Physical activity and amyloid beta in middle-aged and older adults: A systematic review and meta-analysis - María Rodriguez-Ayllon; Patricio Solis-Urra; Cristina Arroyo-Ávila; Miriam Álvarez-Ortega; Pablo Molina-García; Cristina Molina-Hidalgo; Manuel Gómez-Río; Belinda Brown; Kirk I. Erickson; Irene Esteban-Cornejo (Elsevier, 2024)
Background: One of the pathological hallmarks distinguishing Alzheimer's disease from other dementias is the accumulation of amyloid beta (Aβ). Higher physical activity is associated with decreased dementia risk, and one potential path could be through Aβ levels modulation. We aimed to explore the relationship between physical activity and Aβ in middle-aged and older adults. Methods: A systematic search of PubMed, Web of Science, PsycINFO, Cochrane Central Register of Controlled Trials, and SPORTDiscus was performed from inception to April 28, 2022. Studies were eligible if they included physical activity and Aβ data in adults aged 45 years or older. Multi-level meta-analyses of intervention and observational studies were performed to examine the role of physical activity in modulating Aβ levels. Results: In total, 37 articles were included (8 randomized controlled trials, 3 non-randomized controlled trials, 4 prospective longitudinal studies, and 22 cross-sectional studies). The overall effect size of physical activity interventions on changes in blood Aβ was medium (pooled standardized mean difference = -0.69, 95% confidence interval (95%CI): -1.41 to 0.03; I2 = 74.6%). However, these results were not statistically significant, and there were not enough studies to explore the effects of physical activity on cerebrospinal fluid (CSF) and brain Aβ. Data from observational studies were examined based on measurements of Aβ in the brain using positron emission tomography scans, CSF, and blood. Higher physical activity was positively associated with Aβ only in the CSF (Estimate r = 0.12; 95%CI: 0.05-0.18; I2 = 38.00%). Conclusion: Physical activity might moderately reduce blood Aβ in middle-aged and older adults. However, results were only near statistical significance and might be interpreted with caution given the methodological limitations observed in some of the included studies. In observational studies, higher levels of physical activity were positively associated with Aβ only in CSF. Therefore, further research is needed to understand the modulating role of physical activity in the brain, CSF, and blood Aβ, as well as its implication for cognitive health.